POSTPARTUM FOLLICULAR DEVELOPMENT AND ITS INFLUENCE ON SUBSEQUENT REPRODUCTION IN BUFFALOES - AWASTHl, M K; KAVANI, F S; DHAMI, A J; PANCHAL, M T (The Indian Journal of Animal Reproduction, 2023)
Early postpartum ovarian follicular activity was studied to test the hypothesis that the presence ofa large follicle 10 mm in diameter in the ovary ipsilateral to the previously gravid uterine horn betweenDays 14 and 28 postpartum improves subsequent reproductive performance in water buffaloes. Freshlycalved, suckled Mehsana buffaloes (n = 20) were subjected to daily ovarian ultrasound imaging betweenDay 14 and 28 postpartum. The direction of first postpartum large follicle (10 mm) in relation to pastgravid uterine horn was determined. Animals were divided into two groups based on location of a largefollicle on the ovary ipsi- (Group A) and contralateral (Group B) to past gravid uterine horn. First postpartumovulation, first postpartum estrus, calving to conception interval and number of services per conceptionwere recorded. The interval from calving to the detection of first large follicle was significantly higher(P < 0.01) in the animals of Group B (17 .5 ± 1.2 days, n=12) than Group A (22.4 ± 1.7 days, n=8) up toDay 28 postpartum. First postpartum ovulation occurred significantly earlier (P < 0.05) in animals otGroup B ( 18.3 ± 1.5 days, n=7) than in animals of Group A (23.3 ± 1.2 days, n=7) up to Day 28postpartum . The location of a large follicle on either the ovary ipsi- or contralateral to the uterine horncarrying the previous conceptus did not significantly affect the occurrence of the first postpartum estrus(57.9 ± 5.8 versus 56.6 ± 10.5 days), the calving to conception interval (68.4 ± 15.0 versus 91.8 ± 12.9days) or the number of services per conception (1.4 ± 0.3 versus 1.7 ± 0.2). It was concluded that thedata did not support the hypothesis that the presence of a large follicle in the ovary ipsilateral to thepreviously gravid uterine horn during the early postpartum period improved the subsequent reproductiveperformance of water buffaloes.
Keywords: Follicular_growth; Reproductive performance; Water buffalo